JUDICIAL DISPARITIES IN LEGAL INTERPRETATION: THE APPLICATION OF PROGRESSIVE LAW IN MARRIAGE DISPENSATION RULINGS - Kurniawan, Ardian; Dedi Sumanto; Ana Ramadhona; Hendri. K (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose: This study aims to analyze the disparity in judicial interpretations and the application of legal progressivism in marriage dispensation decisions at the Muara Bulian Religious Court. This study seeks to explore how judges construct legal reasoning when faced with applications for underage marriage dispensation and whether their decisions reflect consistency or divergence in applying child protection principles. Methods - This study employs a socio-legal approach with qualitative methods. Data were obtained from case decisions, field observations, and interviews with judges at the Muara Bulian Religious Court. The data were analyzed thematically to identify patterns of judicial interpretation and the extent of progressivism in the rulings’ content. Findings - The results reveal a disparity in judges’ interpretations, particularly regarding the use of progressive legal reasoning. Some judges strictly adhere to statutory provisions, while others accommodate sociocultural considerations and parental requests, resulting in inconsistent outcomes. Although progressive legal theory provides opportunities for child protection, in practice, dispensations are often granted, thereby reinforcing early marriage practices instead of preventing them. Contribution/Limitation of Research: This study contributes to the discourse on judicial discretion and progressive legal thought in the context of family law adjudication. However, it is limited to the Muara Bulian Religious Court; thus, its findings cannot be generalized to all religious courts in Indonesia. Originality/Value - This study highlights the tension between statutory child protection norms and judicial discretion in marriage dispensation cases. It offers a critical socio-legal perspective on how progressivism is interpreted and practiced at the local courts.